Adverse cardiovascular effects of acute salt loading in young normotensive individuals - Tzemos, Nikolaos; Lim, Pitt O; Wong, Suzanne; Struthers, Allan D; MacDonald, Thomas M (Hypertension (Dallas, Tex. 1979), 2008)
We sought to explore the effects of salt loading in young normotensives on vascular endothelial function, echocardiographic left ventricular diastolic function, and electrocardiographic QT dispersion. Sixteen healthy normotensive male volunteers were randomized in a double-blind crossover fashion to 5-day treatment periods with either placebo or salt tablets (200 mmol/d of sodium) separated by a 2-week washout period. Throughout the study the volunteers were asked to maintain a low-salt diet. Forearm venous occlusion plethysmography and intraarterial infusions of acetylcholine (ACh), sodium nitroprusside (SNP), and N(G)-monomethyl-l-arginine (L-NMMA) were used to assess vascular reactivity. Baseline and postsalt loading 12-lead ECGs and echocardiograms were also obtained. Twenty-four-hour ambulatory systolic blood pressure rose (117+/-11 to 121+/-8 mm Hg) significantly with salt loading. The endothelium-dependent responses to ACh were significantly blunted with salt compared to placebo (DeltaFBF% 403 [50] versus 296 [31]; P<0.05) and L-NMMA (DeltaFBF% -47.2 [4] versus -31 [3]; P<0.01). In contrast, the endothelium-independent response to SNP was not different between treatments. Color M-mode flow propagation velocity (CMMFPV), a preload index of left ventricular diastolic function, was significantly reduced with salt (64 [6] versus 59 [16] cm/s; P<0.05) suggesting increased ventricular stiffness. QT dispersion was also significantly increased with salt (58 [16] versus 48 [17] ms; P=0.02). Salt loading impaired vascular endothelial function, left ventricular mechanical relaxation, and electric repolarization in young healthy normotensives.